Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s10067-022-06268-y
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities in systemic lupus erythematosus—a narrative review

Abstract: Purpose of review To describe root causes of health disparities by reviewing studies on incidence and outcomes of systemic lupus erythematosus (SLE) related to ethnic, race, gender, or socioeconomic differences and to propose solutions. Recent findings SLE outcomes have steadily improved over the past 40 years but are not uniformly distributed across various racial and ethnic groups. Belonging to racial and ethnic minority has been cited as a risk factor for more severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 95 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…The absence of differences in local ancestry according to the presence versus absence of more severe disease manifestations suggests that local ancestry is not a large contributor to the observed differences in SLE manifestation severity in African American and Mestizo patients in this study. Although some studies have suggested that genetics may be responsible for the observed differences, recent studies suggest that social determinants of health are a large contributor to these differences 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of differences in local ancestry according to the presence versus absence of more severe disease manifestations suggests that local ancestry is not a large contributor to the observed differences in SLE manifestation severity in African American and Mestizo patients in this study. Although some studies have suggested that genetics may be responsible for the observed differences, recent studies suggest that social determinants of health are a large contributor to these differences 19 …”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that genetics may be responsible for the observed differences, recent studies suggest that social determinants of health are a large contributor to these differences. 19 A major strength of our study was the use of a clinically wellcharacterized multiethnic patient with SLE cohort allowing for analyses to extend beyond populations of European descent. Although SLE is more prevalent and severe in African American and Mestizo populations, multiethnic studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing disparity in sarcoidosis requires a multipronged approach (Fig. 2) [94]. This approach identifies the factors known to influence health disparity within a specific setting and provides solutions that can be implemented at the patient, physician, and legislative level (Table 2).…”
Section: Addressing Disparity With a Goal To Improving Outcomes In Pa...mentioning
confidence: 99%
“…SLE disproportionately affects women and racial or ethnic minority populations, and health disparities have been described for SLE incidence, prevalence, outcomes, and mortality. 1 The most significant contributor to mortality overall in SLE is the presence of renal disease, and renal disease is more common in racial and ethnic minorities. 1 Renal disease also necessitates more aggressive management with immunosuppressant medications.…”
Section: Editorialmentioning
confidence: 99%